Efficiency of Indonesia's Regional Development Banks: Evidence from a Non-Parametric Data Envelopment Analysis Method - Aisyah Camelia Andani; Alvin Sugeng Prasetyo; Danang Nugroho (Jurnal Ekonomi Pembangunan, 2023)
This study aims to determine the level of performance efficiency of Regional Development Banks in Indonesia. This study uses Data Envelopment Analysis with a non-parametric Banker-Charnes-Cooper model approach to investigate variable return to scale, variable projections, and panel data regression. Input variables include third-party funds, non-interest expenses, interest expenses, and employee costs, while output variables include loans, interest income, and operating income apart from interest with control variables namely net interest margin, operating costs to operating income, loan-to-deposit ratio, and capital adequacy ratio. The findings show that net interest margin, operational costs on operational income, loan-to-deposit ratio, and capital adequacy ratio have a positive and significant effect on the efficiency of Regional Development Banks in Indonesia. However, we found that on average Regional Development Banks in Indonesia were still not efficient in carrying out their operational activities, although some showed quite good performance in the IRS, CRS, and DRS situations during the observation period which had implications for the performance of Regional Development Banks which was not yet optimal.